(untitled) (LACCEI, 2024)
This article presents a systematic review on the relationship of New Product Development (DNP), Supply Chain Management (GCS) and the implementation of technologies associated with Industry 4.0 (I4.0) that improve the performance of organizations. . To achieve this goal, a systematic literature review was developed to compile existing literature, identify current research gaps, and systematize research on the relationship of DNP, GCS, and I4.0 with Organizational Performance. In total, twenty-eight (28) articles indexed in Scopus were analyzed. The authors agree that the technologies associated with Industries 4.0 contribute to the Performance of organizations by improving the integration of customers and suppliers in the Supply Chain Management processes while making the development of new products more efficient. new products. From the in-depth analysis of the articles, it was possible to group them into six emerging themes: Organizational Performance, Sustainable Business, Green Organizations, Small and Medium Industries, Product/Service and Process Innovation, and Industry 4.0 Implementation.